2021
DOI: 10.3390/futuretransp1030036
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Technology Survey for Obstacle Detection in Vegetation

Abstract: This study reviews obstacle detection technologies in vegetation for autonomous vehicles or robots. Autonomous vehicles used in agriculture and as lawn mowers face many environmental obstacles that are difficult to recognize for the vehicle sensor. This review provides information on choosing appropriate sensors to detect obstacles through vegetation, based on experiments carried out in different agricultural fields. The experimental setup from the literature consists of sensors placed in front of obstacles, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Li et al implements single-target tracking based on the Kalman flter in the polar coordinate system and uses the threshold method to discriminate and assign targets to enable tracking of vehicles with multiple targets [14]. Lohar et al proposed a convolutional neural network (CNN) model that simulates the point cloud data of the MMW radar and realizes the segmentation of the traversable area of the road [15]. Jin et.al.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al implements single-target tracking based on the Kalman flter in the polar coordinate system and uses the threshold method to discriminate and assign targets to enable tracking of vehicles with multiple targets [14]. Lohar et al proposed a convolutional neural network (CNN) model that simulates the point cloud data of the MMW radar and realizes the segmentation of the traversable area of the road [15]. Jin et.al.…”
Section: Introductionmentioning
confidence: 99%
“…Variations and combinations of the mentioned systems often depend on the configuration of the protected object, area, terrain configuration and vegetation. It can be observed that the combination of several systems gives a more reliable detection and a lower probability of interfering with the system [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the traditional visual localization techniques based on monocular [33,34] or binocular cameras [35] are easily influenced by unfavorable illumination conditions in the underground, resulting in low accuracy of underground target recognition and large distance calculation errors. Compared to monocular or binocular cameras, depth-sensing cameras can carry out active ranging and they are robust to dark environments [36][37][38]; they have good application prospects in underground coal mines. Nevertheless, most of the depth-image based localization techniques need to locate the target carrying a camera [39], which may incur high deployment costs due to the high mobility of underground personnel and equipment.…”
Section: Introductionmentioning
confidence: 99%